1983
DOI: 10.1128/jcm.17.5.830-833.1983
|View full text |Cite
|
Sign up to set email alerts
|

Influence of age, sex, and diet on asymptomatic colonization of infants with Clostridium difficile

Abstract: A total of 40% of 107 stool samples from infants 1 to 52 weeks of age were found to contain Clostridium difficile antigens, detected by counterimmunoelectrophoresis. Within the group tested, there was no detectable variation by age or sex. Infants fed formula were nearly four times more likely to carry C. difficile than were those exclusively breast fed (62 versus 16%), whereas breast-fed infants also receiving formula or solids had an intermediate rate of colonization (35%). The distributions were similar whe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
24
0

Year Published

1985
1985
2012
2012

Publication Types

Select...
5
2
1

Relationship

0
8

Authors

Journals

citations
Cited by 60 publications
(26 citation statements)
references
References 20 publications
2
24
0
Order By: Relevance
“…In this study, only one isolate from the hospitalized patients was tested as normal procedure when studies for toxigenic and non-toxigenic C. difficile were carried out. The distribution of toxigenic and non-toxigenic strains in three different population groups in Denmark was as expected from other studies (4,5,8,19,22), with a higher frequency of toxin producing isolates from hospitalized adults than from hospitalized or healthy children. The explanation may be that toxin-producing strains induce diarrhoea and therefore, in comparison with non-toxigenic strains, have a higher ability to spread among patients.…”
Section: Discussionsupporting
confidence: 87%
See 1 more Smart Citation
“…In this study, only one isolate from the hospitalized patients was tested as normal procedure when studies for toxigenic and non-toxigenic C. difficile were carried out. The distribution of toxigenic and non-toxigenic strains in three different population groups in Denmark was as expected from other studies (4,5,8,19,22), with a higher frequency of toxin producing isolates from hospitalized adults than from hospitalized or healthy children. The explanation may be that toxin-producing strains induce diarrhoea and therefore, in comparison with non-toxigenic strains, have a higher ability to spread among patients.…”
Section: Discussionsupporting
confidence: 87%
“…It is a potent cytotoxin with a damaging effect on cellular microfilaments (7). Cases of chronic and fatal infections are well known (1 7, 21), but in addition clinical asymptomatic carriers of toxigenic C. dijjficile, especially amongst children below the age of one year, have been described (4,5,8,19,22). The purpose of this study was to establish a specific polymerase chain reaction (PCR) method for demonstration of C. difficile toxin A and B genes, to compare this to a McCoy cell line cytotoxicity assay, and to examine strains of C. difficile from different populations.…”
mentioning
confidence: 99%
“…On the influence of diet on asymptomatic colonization of C. difficile, the number of organisms harbored in newborn infants fed form-ula was more than in breast-fed newborn infants (5,13). The present result seems to coincide with those results.…”
Section: Feeding Scores and The Number Of C Difficilesupporting
confidence: 88%
“…DISCUSSION C. difficile is not only accepted as the most important cause of PMC, but is also widely isolated from feces obtained from both healthy adults and newborn infants. The isolation frequency in healthy newborn infants was higher than 30-50% in some reports it was more than 90%; but in healthy adults 10% or less of healthy individuals harbor C. difficile in the intestinal tract (4,5,11,12,16). Our data showed that the ratio of C. diffici/e-positive feces from infants younger than 10 days of age, infants at an age of 10 days to younger than 20 days, infants at an age of 20 days to younger than 30 days and infants older than 30 days were 30.8% (n=13), 70.6% (n = 17 ) , 85.3 % (n = 7) and 100% (n = 8) , respectively.…”
Section: Feeding Scores and The Number Of C Difficilementioning
confidence: 95%
“…The colonization rate of C. difficile varies depending on health status and age (Cooperstock et al, 1983;Tullus et al, 1989). The numbers vary from 4-15% in healthy adults to >70% in infants (Bartlett, 1994;Kato et al, 2001).…”
Section: Epidemiologymentioning
confidence: 99%